Immunohistochemical Analysis of P63 Expression in Odontogenic Lesions. (24th November 2013) - Atarbashi Moghadam, Saede; Atarbashi Moghadam, Fazele; Mokhtari, Sepideh; Eini, Ebrahim
Abstract : P63 may have a role in tumorigenesis and cytodifferentiation of odontogenic lesions. We investigated the immunohistochemical expression of P63 in a total of 30 cases of odontogenic cysts and tumors. The percentage of positive cells was calculated in the lining of odontogenic cysts and islands of ameloblastoma. P63 expression was evident in all types of odontogenic lesions. P63 was expressed throughout the lining epithelium of odontogenic keratocyst except surface parakeratinized layer. In addition, calcifying odontogenic cyst showed P63 expression in all layers. In almost all radicular and dentigerous cysts, the basal and parabasal layers were immunoreactive. Peripheral cells of ameloblastoma expressed P63; however, stellate reticulum had weaker immunostaining. No significant difference in P63 expression was observed between studied lesions (P = 0.86 ). Expression of P63 in odontogenic lesions suggests that this protein is important in differentiation and proliferation of odontogenic epithelial cells. However, it seems that it could not be a useful marker to differentiate between aggressive and nonaggressive lesions. P63 also represents a progenitor or basal cell marker, and it is not expressed in mature differentiated cells.